Development of an Air Coil Superconducting Fault Current Limiter - Näckel, Oliver (Karlsruher Schriftenreihe zur Supraleitung / Hrsg. Prof. Dr.-Ing. M. Noe, Prof. Dr. rer. nat. M. Siegel, 2016)
Electrical power grids are the lifeline of technical infrastructure and fundamental for industry and modern lives. Fault Currents can disrupt the continuous supply of electrical energy, cause instable grid conditions and damage electrical equipment. The Air Coil Superconducting Fault Current Limiter (AC-SFCL) is a measure to effectively limit fault currents. The concept is investigated and proven experimentally by designing, building and successfully testing a 60 kV, 400 V, z = 6% demonstrator.